Preparation and Characterization of Chitosan Nanoparticles-Doped Cellulose Films with Antimicrobial Property - Pang, Suh Cem; Chin, Suk Fun; Ain Nadirah, Romainor; Lesley, Maurice Bilung (Hindawi Publishing Corporation, 2014)
Cellulose films with antimicrobial property were prepared by incorporation of chitosan nanoparticles as antimicrobial agents into the cellulose films. The antimicrobial property of these chitosan nanoparticles-doped cellulose films against Escherichia coli (E. coli) was evaluated via diffusion assay method, minimum inhibitory concentration (MIC) method, and minimum bactericidal concentration (MBC) method. The effects of antimicrobial agent amount, size-related property (nanoparticles and bulk chitosan), and crosslinking by citric acid on antimicrobial activity of cellulose films were studied. It was observed that the antimicrobial activity was enhanced when chitosan nanoparticles were used as compared to when bulk chitosan was used. A maximum E. coli inhibition of 85% was achieved with only 5% (v/v) doping of chitosan nanoparticles into the cellulose films. Crosslinking of the cellulose films with citric acid was observed to have resulted in 50% reduction of water absorbency and a slight increase of E. coli inhibition by 3% for chitosan nanoparticles-doped cellulose films.